Requirements processing for building design: a systematic review - Camila Pegoraro; Istefani Carísio de Paula (Production)
Abstract Problems in buildings can often be traced back to the requirements processing in the design phases. In building design, requirements processing is mainly discussed under the term briefing and is a critical and a problematic process. This study focus on the design stage and aims to summarize and analyze requirements’ processing concepts and practices by a systematic review. The main problems, guidelines, tools and methods were analyzed and compared to the requirements engineering and management approaches. The findings indicate lack of consensus about key concepts and about the coverage of requirements processing, lack of applied methods and lack of practitioners’ knowledge. From the gaps, we proposed a definition for the key concepts, and scheme of this whole requirements processing in building design and indicate recommendations for future research, which can guide important contributions, especially if supported by practical experiences.